Software security readiness index for remote working employee in public organization: Preliminary study - Hakimi, Halimaton Saadiah; Abdullah, Raihana Syahirah; Kamalrudin, Massila (Human Resource Management Academic Research Society, 2024)
The COVID-19 pandemic necessitated a rapid shift to remote working, compelling employees in public organizations to rely heavily on software facilitated by the Internet. This sudden transition, combined with limited guidance, exposed organizations to heightened software security risks, potentially affecting their overall performance. In response, this preliminary study investigates the software security readiness of remote working employees in public organizations. Through a systematic literature review, common security challenges faced by remote workers were identified, along with key factors influencing software security. However, to ensure the relevance and applicability of these factors, a survey was conducted to empirically validate them. The survey targeted remote working employees in public organizations, aiming to uncover current challenges and evaluate the significance of the identified software security factors. The findings from the survey offer critical insights into the prevalent security issues and the effectiveness of the factors in mitigating these risks. This research contributes to the understanding of software security readiness in remote working environments, providing a foundational framework for public organizations to enhance their software security posture. The results emphasize the importance of proactive security measures and awareness among employees to safeguard organizational assets in the evolving landscape of remote work.